ACCOUNTING IN TERMS OF SUSTAINABILITY: A VIEW FROM THE ALTERNATIVE ECONOMIC DEVELOPMENT - Mejía Soto, Eutimio (2015)
Accounting as a science has been built from various epistemological, sociological, political and economic concepts- among other fields of knowledge- that influence the accounting discursive universe, prevailing comprehensive, holistic, inclusive and ethical vision related to the welfare of present and future society.Accounting regulation is not necessarily derived from research; therefore, it has maintained a reductionist tendency of its knowledge, conceiving accounting as the language of business, with no more responsibility than the protection and safeguard the interest of venture capital providers.This paper aims to contribute to the theoretical construction and practical design of an accounting for sustainability, understood as a knowlegde socio-environmentally responsible for contributing to the protection of the environmental, social and economic richness, through management assessment organizations made regarding the aforementioned richness. Accounting for sustainability is built on dialoguing with the Natural Sciences and the Social Sciences. The bioaccounting and socioaccounting like other emerging disciplines, are oriented towards ecological and social sustainability, where economic and financial aspects should be at the service of nature and society.